The political thought of Václav Havel : philosophical influences and contemporary applications - Brennan, Daniel, 1982- (Value Inquiry Book Series, 2017)
The book considers Václav Havel's body of writing as a cohesive whole offering a consistent political philosophy. This bold claim is backed up through a close examination of Havel's plays, letters, essays and aphorisms. The political philosophy that a close reading of Havel reveals is a liberal one. However, Havel is not the run-of the-mill liberal having influences from the field of phenomenology, Masaryk, Husserl, Levinas Patočka and Heidegger which give him a nuanced view of the self. Havel sees the self as something always being formed. Hence for Havel man has an ability to 'shake' his current state and invite transcendence into his life. This agonistic process reveals our responsibility and liberates the self from forces which coerce behaviour.